2017
DOI: 10.1002/jca.21570
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasma exchange, leukocytapheresis, and plasma diafiltration in management of refractory macrophage activation syndrome

Abstract: Macrophage activation syndrome (MAS) is a life-threating complication of systemic juvenile idiopathic arthritis (s-JIA). Steroid and cyclosporine (CsA) are effective for MAS, but, treatment for steroid-and CsA-resistant patients is still challenging. We report the case of steroid and CsA resistant s-JIA associated MAS misdiagnosed as Kawasaki disease (KD), who was successfully treated with the combination of plasma exchange (PE) and leukocytapheresis (LCAP) followed by plasma diafiltration (PDF). PE 1 LCAP eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Previous studies have suggested that therapeutic plasma exchange plays an important role in the treatment of severe HLH [85, 86]. Similarly, high‐volume haemofiltration has also been reported to improve organ function in critically ill children with HLH by reducing the levels of cytokines (such as TNF‐α and IL‐6) [87].…”
Section: Potential Therapeutic Options For Css In Covid‐19mentioning
confidence: 99%
“…Previous studies have suggested that therapeutic plasma exchange plays an important role in the treatment of severe HLH [85, 86]. Similarly, high‐volume haemofiltration has also been reported to improve organ function in critically ill children with HLH by reducing the levels of cytokines (such as TNF‐α and IL‐6) [87].…”
Section: Potential Therapeutic Options For Css In Covid‐19mentioning
confidence: 99%
“…Therapeutic plasma exchange removes endogenous and exogenous inducers of the systemic inflammatory response (pathogen-associated molecular pattern and damage-associated molecular pattern) and proinflammatory mediators (cytokines and reactive oxygen species) that are involved in the pathogenesis of organ failure ( 8 ). Sporadic case reports suggest that therapeutic plasma exchange can be an effective rescue therapy in patients with hemophagocytic lymphohistiocytosis ( 9 ) or severe influenza A (H1N1) infection ( 10 ). We report a case series of four critically ill patients infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) successfully treated with plasma exchange.…”
mentioning
confidence: 99%
“…Although there have been a couple of positive case reports on the additive use of PE in MAS-HLH, for example due to sJIA which constitutes the leading underlying condition of MAS-HLH in children, 2,17,25,26 HLH following solid organ transplantation, 14 and promising case series on supportive use of PE in children with MAS, 27 none of the authors evaluated PE as first-line intervention to steroid refractory cases. Although most of our patients showed partial responses to PE, which mainly blunted fever, none showed resolving HLH and all required additional escalation of immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%